2012
DOI: 10.1007/s00343-012-1038-6
|View full text |Cite
|
Sign up to set email alerts
|

Ecological effects of co-culturing sea cucumber Apostichopus japonicus (Selenka) with scallop Chlamys farreri in earthen ponds

Abstract: Monthly changes in sedimentation and sediment properties were studied for three different culture treatments: sea cucumber monoculture (Mc), sea cucumber and scallop polyculture (Ps-c) and scallop monoculture (Ms). Results indicated that the survival rate of sea cucumber was significantly higher in Ps-c cultures than in Mc cultures. Sea cucumber yield was 69.6% higher in Ps-c culture than in Mc culture. No significant differences in body weight and scallop shell length were found between Ps-c and Ms cultures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Increasingly, complex multitrophic pond systems are being commercially piloted in China with larger juvenile A. japonicus stocked at high densities (~10 g at density of 10 ind m À2 ) in IMTA with other species such as the scallop Chlamys farreri, and the jellyfish, Rhopilema esculentum, the crab Charybdis japonica, and shrimps Penaeus japonicus and Fenneropenaeus chinensis in varying combinations (Zheng et al 2009;Ren et al 2012bRen et al , 2014Feng et al 2014;Li et al 2014a,b).…”
Section: Commercial and Experimental Integration Of Sea Cucumbers Intmentioning
confidence: 99%
“…Increasingly, complex multitrophic pond systems are being commercially piloted in China with larger juvenile A. japonicus stocked at high densities (~10 g at density of 10 ind m À2 ) in IMTA with other species such as the scallop Chlamys farreri, and the jellyfish, Rhopilema esculentum, the crab Charybdis japonica, and shrimps Penaeus japonicus and Fenneropenaeus chinensis in varying combinations (Zheng et al 2009;Ren et al 2012bRen et al , 2014Feng et al 2014;Li et al 2014a,b).…”
Section: Commercial and Experimental Integration Of Sea Cucumbers Intmentioning
confidence: 99%
“…Slater & Carton (2009) made a similar observation with Australostichopus mollis in coastal sediments impacted by mussel farm deposits. Furthermore, in an integrated system of sea cucumber A. japonicus with scallop Chlamys farreri, Ren et al (2012) observed a decline in TOC as a result of sea cucumber feeding, but there was an increase in TOC in sediments during periods of sea cucumber dormancy. Sediment reworking and organic matter uptake by holothurians could depend on individual numbers and sizes, food availability and local conditions (Dar & Ahmad 2006).…”
Section: Tom and Toc In Sedimentmentioning
confidence: 99%
“…The potential for mussel production that was based on particulate wastes, however, was far lower than for seaweed because of fewer initial available resources and the metabolic losses of mussels . Most of the particles originating from fish faeces or uneaten feed may sediment out near the cages (Elberizon & Kelly 1998); such wastes may be better utilised by co-cultured depositfeeding species, for example sea cucumbers, and the nutritional value of the particle wastes released from fish farming should be more closely evaluated (Gré-mare et al 1997, Ahlgren 1998, Ren et al 2012.…”
Section: Introductionmentioning
confidence: 99%